(untitled) (AYUSHDHARA, 2023)
Sira Shareera is a chapter dealt under Shareera Sthana of Sushruta Samhita, that deals with description regarding vascular entity and its distribution and function in the body. In Sushruta Samhita specific colours are mentioned for different kinds of Sira based on conducting material. Aruna Varna for Vatavaha Sira, Neela Varna for Pittavaha Sira, Gourya Varna for Kaphavaha Sira and Rohini Varna for Raktavaha Sira. These colours of the Sira depends on the nature and colour of material conducting through these Sira. The word Sira is not confined only to one type of structural entity but is used for tubular vessels of the body such as nerve, vein, artery, lymph vessels etc. In such condition it is very difficult to understand the concept of Sira doubtlessly in terms of modern anatomy. Therefore, it requires critical literature review and analytical probe to understand the concept of Sira.